EFFICACY OF CERVICAL NERVE TENSION ASSESSMENT SCREENING TOOL AMONG SUBJECTS WITH CERVICAL RADICULOPATHY - Kabra, Amruta; Shinde, Sandeep (International Journal of Psychosocial Rehabilitation, 2020)
Background In cervical radiculopathy, inflamed and damaged nerve roots alter the neurological function. Numbness, weakness, radiating pain from neck to shoulder, arm, hand, or fingers. Electrodiagnostic studies play a crucial role in diagnosing disorders of nerves and muscles, but they are expensive and have a large setup. Portable nerve conduction devices are very easy to use, simple and inexpensive, and cost-effective means of measurement. There are very limited scales of Android applications and portable screening tools for nerve conduction studies. Aim and objectives 1. To study and find the efficacy of the cervical nerve tension assessment screening tool among subjects with cervical radiculopathy. 2 To compare the readings of ulnar and median nerve conduction velocity by using newly developed cervical nerve tension assessment screening tool with the conventional diagnostic device on healthy as well as cervical radiculopathy subjects materials and methodology There were 124 participants; they were allocated into two groups with 62 participants each. Group A was of subjects with cervical radiculopathy, and group B was of healthy individuals, and they were diagnosed by a standard existing NCS device and simultaneously by a newly developed screening tool, which is portable. Nerve conduction and latency were outcome measures in both devices for median and ulnar motor nerves. At the end, data were analyzed, and the values of the new device were compared with the existing device to check the accuracy. Result: There is a perfect and significant correlation observed between existing and portable devices in all parameters. The value for median and ulnar nerve latency and conduction velocity in both groups is <0.001, meaning it is very significant. Conclusion The Cervical Nerve Tension Assessment Screening Tool among subjects with cervical radiculopathy can be an alternative to the existing NCS device. The readings of the cervical nerve tension assessment screening tool match with the standard existing device of NCS.